2016
DOI: 10.1007/s10120-015-0588-7
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative bleeding after gastric endoscopic submucosal dissection in patients receiving antithrombotic therapy

Abstract: Background and aims It is controversial whether antithrombotic therapy increases the risk of bleeding after endoscopic submucosal dissection (ESD). The aim of this study was to evaluate the effects of antithrombotic therapy on gastric ESD. Methods Patients who underwent gastric ESD at Toranomon Hospital between April 2005 and July 2014 were enrolled. The risk of post-ESD bleeding was evaluated by multivariate logistic regression analysis. Results Of 1781 patients enrolled, 253 were taking an antithrombotic; 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 27 publications
7
53
1
Order By: Relevance
“…Moreover, bleeding has been associated with high bleeding risk procedures and taking warfarin with heparin bridging [29, 30]. Furuhata et al [31] and Yoshio et al [22] also reported that heparin alternative therapy significantly increases the risk of post-ESD bleeding for EGC [22, 31]. Our data also showed that bleeding after gastric ESD occurred in 14% of patients taking warfarin with heparin bridging.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, bleeding has been associated with high bleeding risk procedures and taking warfarin with heparin bridging [29, 30]. Furuhata et al [31] and Yoshio et al [22] also reported that heparin alternative therapy significantly increases the risk of post-ESD bleeding for EGC [22, 31]. Our data also showed that bleeding after gastric ESD occurred in 14% of patients taking warfarin with heparin bridging.…”
Section: Discussionsupporting
confidence: 69%
“…However, they elaborated that postoperative bleeding occurred later in patients who ceased aspirin treatment compared to those who continued taking aspirin [32]. Between the findings of previous studies and our studies, we found that there were some differences in terms of the risk of the cessation of antithrombotic therapy [24,26,27,33]. These discrepancies may be accounted for by the differences in the numbers and types of antithrombotic agents mentioned in these studies.…”
Section: Discussioncontrasting
confidence: 54%
“…However, whereas few reports have evaluated the safety of antithrombotic therapy in high-risk procedures such as ESD before the revision of the JGES2012 guideline 19 20 , several reports have evaluated the safety after the revision of the guideline 21 22 23 . For example, Igarashi et al 21 reported that the delayed bleeding rate associated with gastric ESD was significantly higher in patients receiving antithrombotic therapy than in those not receiving such therapy; this included procedures under both cessation and continuation of antiplatelet agents.…”
Section: Introductionmentioning
confidence: 99%